Answer:
[tex]\log_{3} ({5\sqrt{x}} * y ) = \log_{3}({5) + \log_{3}(\sqrt{x}) +\log_{3}( y )[/tex]
Step-by-step explanation:
Given
[tex]\log_{3} ({5\sqrt{x}} * y )[/tex]
Required
Write as sum or difference
Using addition law of logarithm, the equation becomes:
[tex]\log_{3} ({5\sqrt{x}} * y ) = \log_{3}({5\sqrt{x}) +\log_{3}( y )[/tex]
Expand
[tex]\log_{3} ({5\sqrt{x}} * y ) = \log_{3}({5 * \sqrt{x}) +\log_{3}( y )[/tex]
Apply addition law
[tex]\log_{3} ({5\sqrt{x}} * y ) = \log_{3}({5) + \log_{3}(\sqrt{x}) +\log_{3}( y )[/tex]